Finite-time stability of a class of continuous-time non-homogeneous switched systems. (November 2017) - Kuiava, Roman; Matos, Bruna Krasota; Razente, Gustavo Reche
Abstract: This paper is concerned with the finite-time stability problem of a class of linear continuous-time non-homogeneous switched systems under a time-dependent switching signal constrained by a dwell-time T . Once the finite-time stability is guaranteed, one of the main results of the paper guarantees that any system trajectory starting in a subset Ω 1 of the state-space will remain in Ω 2 ⊃ Ω 1 over a finite time interval and for any switching sequence with a dwell-time T ̄ ≥ T . The finite-time stability conditions are provided in the form of bilinear matrix inequalities (BMIs), which can be transformed to linear matrix inequalities (LMIs) by means of a step-by-step procedure that includes the computation of the sets Ω 1 and Ω 2 by the knowledge of the system operating range. Three illustrative examples are used to show the validity of the results.